Porous low-dielectric film and preparation method thereof

Through electrochemical corrosion and grafting technology, the formation of porous low-dielectric films on the surface of single crystal silicon has been solved, and the problem of difficulty in reducing the dielectric constant in the prior art is achieved, and the effective reduction of the dielectric constant and precise control of pore distribution is achieved. Simple and economical method.

CN119480795APending Publication Date: 2025-02-18ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411583879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the pore size and distribution of low-dielectric films, resulting in difficult to effectively reduce the dielectric constant, and the preparation method is complex and costly.

Method used

Porous silicon is formed by electrochemical corrosion on the single crystal silicon and electrochemical grafting on its surface. The devinyl POSS (T10V10) and dodecanoyl POSS (T12V12) monomers with lower graft dielectric constants are selected. , precisely control pore size and distribution, thereby reducing the dielectric constant of the film.

Benefits of technology

The effective reduction of the dielectric constant of the low-dielectric film is achieved, and the problem of difficulty in precise control of the pore size and distribution is solved. The preparation method is relatively simple and economically low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480795A_ABST
    Figure CN119480795A_ABST
Patent Text Reader

Abstract

The invention relates to a low-dielectric porous film and a preparation method thereof, and the preparation method comprises the following steps: S1, carrying out electrochemical corrosion on monocrystalline silicon in an HF electrolyte to obtain porous silicon; wherein the monocrystalline silicon is an anode; s2, dissolving a surfactant, a diazonium salt type initiator, a grafting monomer and an acid solution in a solvent to form a grafting solution; s3, performing electrochemical grafting on the porous silicon in the step S1 in the grafting solution obtained in the step S2 to obtain a porous low-dielectric film; wherein the porous silicon is a cathode. According to the preparation method disclosed by the invention, the porous morphology is etched on the silicon surface in advance by utilizing electrochemical corrosion, so that octavinyl silsesquioxane can be electrochemically grafted, and decavinyl POSS and dodecavinyl POSS with lower dielectric constants can also be effectively grafted; meanwhile, accurate control over the size and distribution of pores in the silicon surface can be achieved through electrochemical corrosion, the dielectric constant of the thin film is further reduced, and the thin film has a better application prospect in the field of high-frequency communication in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of integrated circuit dielectric film preparation, and relates to a porous low-dielectric film and a preparation method thereof. Background Art

[0002] As the demand for mitigating the sharply increasing resistance-capacitance (RC) delay in advanced technology nodes continues to increase, low-k materials are of great significance in the development of integrated circuits. Low-k materials have been proven to be an effective way to reduce RC delay in chip interconnects as interlayer dielectrics (ILDs) in back-end-of-line (BEOL) processes and insulating layers in 3D integration.

[0003] In theory, there are two strategies to reduce the dielectric constant value of the dielectric layer. One is to reduce the polarizability of the molecule by introducing groups that are not easily polarizable in the molecular design, such as CH, CC, C-Si, CO, and CF bonds. So far, low-k value materials such as silicates, dry gels, and some organic polymers have been reported. Another method, introducing pores in the dielectric film is also an effective strategy to reduce the k value; one of the schemes is to pyrolyze the dispersed phase in the block copolymer, and then a foam film with pores can be generated. However, precisely controlling the size and distribution of the pores by this method remains a challenging problem.

[0004] Therefore, there is an urgent need for a new method for preparing low dielectric films that is simple to operate, highly efficient, and low cost. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a low dielectric porous film and a preparation method thereof. The present invention electrochemically etches single crystal silicon to form porous silicon that can not only be electrochemically grafted with octavinylsilsesquioxane (OVS), but can also be effectively grafted with decavinyl POSS (T10V10) and dodecavinyl POSS (T12V12) with lower dielectric constants, thereby reducing the dielectric constant of the film; at the same time, the size and distribution of pores on the silicon surface can be precisely controlled by electrochemical etching, further reducing the dielectric constant of the film, and realizing a dielectric film with a lower dielectric constant.

[0006] The purpose of the present invention can be achieved by the following scheme:

[0007] In a first aspect, the present invention provides a method for preparing a porous low dielectric film, comprising the following steps:

[0008] S1. Electrochemically corroding single crystal silicon in HF electrolyte to obtain porous silicon; wherein the single crystal silicon is the anode;

[0009] S2, dissolving the surfactant, the diazonium salt initiator, the grafting monomer, and the acid solution in a solvent to form a grafting solution;

[0010] S3. In the grafting solution obtained in step S2, the porous silicon in step S1 is subjected to electrochemical grafting to obtain a porous low dielectric film; wherein the porous silicon is a cathode.

[0011] As an embodiment of the present invention, in step S1, the HF electrolyte comprises anhydrous ethanol and HF in a volume ratio of 0.5-2:1.

[0012] As an embodiment of the present invention, in step S1, the current density of the electrochemical corrosion is 5-20 mA / cm 2 If the current density is too high, the pores on the silicon surface will be too large, reducing the mechanical properties of the film; if the current density is too low, the pores on the silicon surface will be too small, and the dielectric constant of the film cannot be effectively reduced.

[0013] As an embodiment of the present invention, in step S1, the cathode material of the electrochemical corrosion includes any one of Pt, graphite, and Au.

[0014] As an embodiment of the present invention, in step S2, the solvent is a tetrahydrofuran-water mixed solvent.

[0015] As an embodiment of the present invention, in step S2, the grafting solution is: for every 50-250 mL of deionized water, 50-250 mL of tetrahydrofuran is added, and then 0.2-1 g of grafting monomer, 0.2-1 g of surfactant, 3-15 mL of acid solution, and 0.3-1.5 g of diazonium salt initiator are added in sequence.

[0016] As an embodiment of the present invention, in step S2, the grafting monomer includes one or more of octavinyl silsesquioxane (OVS), decavinyl POSS (T10V10), and dodecavinyl POSS (T12V12). The preparation method of the present invention can prepare any organic film having vinyl groups and being soluble in a mixed solvent of THF and deionized water on the surface of porous silicon.

[0017] As an embodiment of the present invention, in step S2, the surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate (SDS).

[0018] As an embodiment of the present invention, in step S2, the diazonium salt initiator includes one or more of 4-nitrobenzenediazonium tetrafluoroborate (NBD).

[0019] As an embodiment of the present invention, in step S2, the acid solution includes one or more of hydrochloric acid, tetrafluoroboric acid, nitric acid, and phosphoric acid.

[0020] The acidic ions in the acid solution of the present invention are used to reduce the pH value of the solution, thereby maintaining the stability of the initiator. The surfactant is used to reduce the surface tension between the solution and the silicon substrate, promoting the electrochemical grafting reaction to proceed smoothly. The initiator is used to initiate the cleavage of the ethylene bond and the polymerization reaction to form a film.

[0021] As an embodiment of the present invention, in step S3, the electrochemically grafted anode material includes any one of Pt, graphite, and Au.

[0022] As an embodiment of the present invention, in step S3, the temperature of the electrochemical grafting is 20 to 50° C., and the time is 1 to 500 min.

[0023] As an embodiment of the present invention, in step S3, the electrochemical grafting process uses a pulse voltage, the maximum negative voltage of the pulse voltage output waveform is -5 to -10V, and the duration is t on The minimum negative voltage of the pulse voltage output waveform is -0.5~-3V, and the duration is t off is 90ms.

[0024] The electrochemical grafting of the present invention is an electrochemical grafting technology based on diazonium salt.

[0025] In a second aspect, the present invention provides a porous low dielectric film obtained by the preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention utilizes electrochemical corrosion to pre-etch a porous morphology on a silicon surface, and then utilizes a chemical grafting technique based on a diazonium salt to assemble a porous film on the surface. The selection of monomers for producing the porous film can also be diversified, and not only octavinyl silsesquioxane (OVS) can be grafted, but also decavinyl POSS (T10V10) and dodecavinyl POSS (T12V12) with lower dielectric constants can be grafted, thereby reducing the dielectric constant of the film, solving the problem that conventional immersion-etched silicon substrates cannot be effectively grafted with POSS monomers with lower dielectric constants such as T10V10 and T12V12; at the same time, electrochemical corrosion can also be used to achieve precise control of the size and distribution of pores on the silicon surface, further reducing the dielectric constant of the film, and achieving a dielectric film with a lower dielectric constant.

[0028] 2. Theoretically, the preparation method of the present invention can prepare any vinyl organic film on the surface of porous silicon, so that it has better application prospects in the future high-frequency communication field; by further optimizing the conditions, a uniform nanoporous organic insulating film is obtained, which provides a new idea and method for the preparation of low dielectric organic insulating films. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0030] Figure 1 Schematic diagram of the surface mechanism of silicon corrosion and H passivation;

[0031] Figure 2 This is a scanning electron microscope characterization image of the porous silicon in Example 1;

[0032] Figure 3 Graph 1 shows the relationship between the dielectric constant of the dielectric film and the wavelength (frequency) in Example 1. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0034] It should be noted that if Figure 1 As shown in the figure, during electrochemical corrosion, the silicon atoms on the silicon surface begin to be affected by the synergistic effect of holes and HF, react with water, and produce Si-H bonds and Si-OH bonds (reference formula I); wherein, the Si-OH bond reacts with Si to produce Si-O-Si (reference formula II), which dissolves and corrodes silicon in HF; the Si-H bond is easily attacked by holes due to its weak polarity. Once it encounters holes diffused into the hydrogen passivation layer, F - It will attack the Si-H bond, causing it to break and generate a Si-F bond. As the Si-F bond is generated, it will eventually cut the Si-Si bond. The final result of Si is that all four H are replaced by F, forming SiF4. SiF4 eventually reacts with H + Combine to form H2SiF6, then dissolve.

[0035] Si-Si+H2O→Si-H+Si-OH Formula I

[0036] Si+2Si-OH→Si-O-Si+H + Formula II.

[0037] Example 1

[0038] This embodiment provides a method for preparing a low dielectric porous film, comprising the following steps:

[0039] Step (1): electrochemically corrode single crystal silicon in HF electrolyte at 20°C to obtain porous silicon. Figure 2 This is a scanning electron microscope characterization image of porous silicon. Among them, single crystal silicon is the cathode and Pt is the anode; the electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1, and the current density of electrochemical corrosion is 10mA / cm 2 , time is 60s;

[0040] Step (2): dissolving a surfactant, a diazonium salt initiator, a grafting monomer, and H2SO4 in a tetrahydrofuran-water mixed solvent at a temperature of 20° C. to form a grafting solution;

[0041] The preparation process of the grafting solution is as follows: 20 mL of tetrahydrofuran is added to every 20 mL of deionized water, and then 0.1 g of octavinylsilsesquioxane (OVS) as a grafting monomer, 0.1 g of sodium dodecylsulfonate as a surfactant, 2 mL of H2SO4, and 0.15 g of 4-nitrobenzenediazotetrafluoroborate (NBD) as an initiator are added in sequence;

[0042] Step (3): In the grafting solution obtained in step (2), the porous silicon in step (1) is immediately subjected to electrochemical grafting to obtain a porous low dielectric film. The electrochemical grafting temperature is 20°C and the time is 30 minutes. The porous silicon is connected to the negative electrode of the power supply as a cathode, and the platinum sheet is connected to the positive electrode of the power supply as an anode. The electrochemical grafting process uses a pulse voltage, and the maximum negative voltage of the pulse voltage output waveform is -6V, and the duration t on The minimum negative voltage of the pulse voltage output waveform is -0.5V, and the duration is t off 90ms;

[0043] Step (4): The dielectric properties of the obtained low-k dielectric film covalently grafted on the semiconductor surface are measured using an ellipsometer, and the average dielectric constant k≈1.95 in the range of 600-1700nm (484-225THz) is obtained. The relationship between the dielectric constant and the wavelength (frequency) is shown in the figure.

[0044] Example 2

[0045] Step (1): Electrochemically etch single crystal silicon in HF electrolyte at 20°C to obtain porous silicon. The single crystal silicon is the cathode and Au is the anode. The electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1. The current density of the electrochemical etching is 15 mA / cm 2 , time is 75s;

[0046] Step (2): dissolving a surfactant, a diazonium salt initiator, a grafting monomer, and H2SO4 in a tetrahydrofuran-water mixed solvent at a temperature of 20° C. to form a grafting solution;

[0047] The preparation process of the grafting solution is as follows: 20 mL of tetrahydrofuran is added to every 20 mL of deionized water, and then 0.1 g of decaethylene POSS (T10V10) as a grafting monomer, 0.1 g of sodium dodecyl sulfate as a surfactant, 2 mL of H2SO4, and 0.15 g of 4-nitrobenzenediazotetrafluoroborate (NBD) as an initiator are added in sequence;

[0048] Step (3): In the grafting solution obtained in step (2), the porous silicon in step (1) is immediately subjected to electrochemical grafting to obtain a porous low dielectric film. The electrochemical grafting temperature is 20°C and the time is 40 minutes. The porous silicon is connected to the negative electrode of the power supply as a cathode, and the platinum sheet is connected to the positive electrode of the power supply as an anode. The electrochemical grafting process uses a pulse voltage, and the maximum negative voltage of the pulse voltage output waveform is -8V, and the duration t on The minimum negative voltage of the pulse voltage output waveform is -0.5V, and the duration is t off 90ms;

[0049] Step (4): The dielectric properties of the obtained low-k dielectric film covalently grafted onto the semiconductor surface are measured using an ellipsometer, and an average dielectric constant k≈1.87 is obtained in the range of 600 to 1700 nm (484 to 225 THz).

[0050] Example 3

[0051] Step (1): Electrochemically etch single crystal silicon in HF electrolyte at 20°C to obtain porous silicon. The single crystal silicon is the cathode and graphite is the anode. The electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1. The current density of the electrochemical etching is 18 mA / cm 2 , time is 90s;

[0052] Step (2): dissolving a surfactant, a diazonium salt initiator, a grafting monomer, and H2SO4 in a tetrahydrofuran-water mixed solvent at a temperature of 20° C. to form a grafting solution;

[0053] The preparation process of the grafting solution is as follows: 20 mL of tetrahydrofuran is added to every 20 mL of deionized water, and then 0.1 g of dodecaethylene POSS (T12V12) as a grafting monomer, 0.1 g of sodium dodecylbenzene sulfonate (SDS) as a surfactant, 1.5 mL of H2SO4, and 0.15 g of 4-nitrobenzene diazonium tetrafluoroborate (NBD) as an initiator are added in sequence;

[0054] Step (3): In the grafting solution obtained in step (2), the porous silicon in step (1) is immediately subjected to electrochemical grafting to obtain a porous low dielectric film. The electrochemical grafting temperature is 20°C and the time is 45 minutes. The porous silicon is connected to the negative electrode of the power supply as a cathode, and the platinum sheet is connected to the positive electrode of the power supply as an anode. The electrochemical grafting process uses a pulse voltage, and the maximum negative voltage of the pulse voltage output waveform is -9V, and the duration t on The minimum negative voltage of the pulse voltage output waveform is -0.5V, and the duration is t off 110ms;

[0055] Step (4): The dielectric properties of the obtained low-k dielectric film covalently grafted onto the semiconductor surface are measured using an ellipsometer, and an average dielectric constant k≈1.84 is obtained in the range of 600 to 1700 nm (484 to 225 THz).

[0056] Comparative Example 1

[0057] The preparation method of this comparative example is basically the same as that of Example 1, except that the electrochemical corrosion is replaced by immersion corrosion, specifically:

[0058] Step (1): At a temperature of 20° C., place the single crystal silicon in an HF electrolyte and soak for 60 seconds. The electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1.

[0059] The dielectric properties of the film obtained in this comparative example were measured using an ellipsometer, and an average dielectric constant k≈2.23 was obtained in the range of 600-1700 nm (484-225 THz).

[0060] Comparative Example 2

[0061] The preparation method of this comparative example is basically the same as that of Example 2, except that the electrochemical corrosion is replaced by immersion corrosion, specifically:

[0062] Step (1): At a temperature of 20° C., place the single crystal silicon in an HF electrolyte and soak for 60 seconds. The electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1.

[0063] The dielectric properties of the film obtained in this comparative example were measured using an ellipsometer, and an average dielectric constant k≈2.18 was obtained in the range of 600 to 1700 nm (484 to 225 THz).

[0064] Comparative Example 3

[0065] The preparation method of this comparative example is basically the same as that of Example 3, except that the electrochemical corrosion is replaced by immersion corrosion, specifically:

[0066] Step (1): At a temperature of 20° C., place the single crystal silicon in an HF electrolyte and soak for 60 seconds. The electrolyte is a mixture of anhydrous ethanol and HF in a volume ratio of 1:1.

[0067] The dielectric properties of the film obtained in this comparative example were measured using an ellipsometer, and an average dielectric constant k≈2.06 was obtained in the range of 600-1700 nm (484-225 THz).

[0068] Comparative Example 4

[0069] The preparation method of this comparative example is basically the same as that of Example 1, except that the current density of the electrochemical corrosion in step (1) is 10 mA / cm 2 and time 60 s replaced by a current density of 2 mA / cm 2 and time 15s.

[0070] The dielectric properties of the film obtained in this comparative example were measured using an ellipsometer, and an average dielectric constant k≈2.58 was obtained in the range of 600 to 1700 nm (484 to 225 THz).

[0071] In summary, from Comparative Examples 1-3, it can be seen that, since conventional immersion etching cannot form a porous morphology on the silicon surface, on the one hand, when grafting the OVS monomer, the effect of reducing the dielectric constant is limited; on the other hand, it is impossible to effectively graft monomers such as T10V10 and T12V12, resulting in a high dielectric constant of the formed film. From Comparative Example 4, it can be seen that the present invention controls the current density and time of electrochemical corrosion to make the film have both excellent mechanical properties and low dielectric constant. If it is lower than this range, the dielectric constant will be higher and cannot meet the requirements.

[0072] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a porous low dielectric film, characterized in that: The following steps are involved: S1. Electrochemically corroding single crystal silicon in HF electrolyte to obtain porous silicon; wherein the single crystal silicon is the anode; S2, dissolving the surfactant, the diazonium salt initiator, the grafting monomer, and the acid solution in a solvent to form a grafting solution; S3. In the grafting solution obtained in step S2, the porous silicon in step S1 is subjected to electrochemical grafting to obtain a porous low dielectric film; wherein the porous silicon is a cathode.

2. The preparation method according to claim 1, characterized in that: In step S1, the HF electrolyte includes anhydrous ethanol and HF in a volume ratio of 0.5-2:

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the current density of the electrochemical corrosion is 5-20 mA / cm 2 , time is 30-120s.

4. The preparation method according to claim 1, characterized in that: In step S1, the cathode material for electrochemical corrosion includes any one of Pt, graphite, and Au.

5. The preparation method according to claim 1, characterized in that: In step S2, the grafting solution is: 50-250 mL of tetrahydrofuran is added to every 50-250 mL of deionized water, and then 0.2-1 g of grafting monomer, 0.2-1 g of surfactant, 3-15 mL of acid solution, and 0.3-1.5 g of diazonium salt initiator are added in sequence.

6. The preparation method according to claim 1, characterized in that: In step S2, the grafting monomer includes one or more of octavinyl silsesquioxane, decamethylene POSS, and dodecamethylene POSS.

7. The preparation method according to claim 1, characterized in that: In step S2, the surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the diazonium salt initiator includes one or more of 4-nitrobenzene diazonium tetrafluoroborate; and the acid solution includes one or more of hydrochloric acid, tetrafluoroboric acid, nitric acid, and phosphoric acid.

8. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the electrochemical grafting is 20 to 50° C., and the time is 1 to 500 min.

9. The preparation method according to claim 1, characterized in that: In step S3, the electrochemical grafting process uses a pulse voltage, the maximum negative voltage of the pulse voltage output waveform is -5 to -10V, and the duration is t on The minimum negative voltage of the pulse voltage output waveform is -0.5~-3V, and the duration is t off is 90ms.

10. A porous low dielectric film obtained by the preparation method according to any one of claims 1 to 9.